(untitled) (CIPEEX, 2025)
The current study aims to analyze the scientific evidence available on the effects of metabolic CrossFit on the physiological and health properties of individuals. CrossFit is known for its varied functional movements performed with high intensity. This type of training has gained popularity due to the surprising results it provides in a relatively short period of time. In addition to being effective, it is a dynamic practice and appreciated by practitioners. One of the main advantages of this style of training is the metabolic response it generates, promoted by increased muscle synthesis and the action of anabolic hormones. The study method is a bibliographical review that employs a qualitative approach to data analysis, whose objective is to base the review on theoretical bases regarding the topic in question, with a study based on books, magazines, newspapers, and scientific articles published in the period between 2019 and 2024, in the databases: SciELO, Lilacs, UNICAMP Library, PubMed, and academic repositories. The results indicate that metabolic CrossFit can have significant effects on cardiovascular capacity, these effects are demonstrated by the increase in the maximum volume of oxygen consumed (VO2 maximum) and the efficiency of oxygen consumption. Furthermore, several studies have reported decreases in the percentage of body fat and increases in muscle mass. These studies warn that, for this reason, the body composition of practitioners is affected. Furthermore, glycemic control appears to have increased, with consistent reductions in fasting blood glucose levels observed in several studies. Regarding the lipid profile, there is evidence of a reduction in total and LDL cholesterol, as well as an increase in HDL, which suggests a positive impact on cardiovascular health. The motivating and community-oriented nature of metabolic CrossFit became evident through the study, which can help promote exercise adherence and maintain a healthy lifestyle. However, research suggests that there is a need for preventative measures, specifically for those who are new to the sport and those with pre-existing conditions, due to the potential danger of injury associated with intense training. It was concluded that metabolic CrossFit is a beneficial intervention that promotes metabolic and cardiovascular health, and is also a viable alternative to other quick resolution strategies. Thus, it is observed that, with adequate guidance and individual guidance, the training in question can have a significant role in promoting health and preventing chronic diseases. In this way, the research highlights the value of additional studies that would expand knowledge of the physiological processes involved and explore the safety and metabolic effect of CrossFit in different populations.